Morbidity Related to Incisional Hernia Repair with Abdominoplasty (Medical Forum Monthly, 2020)
Objective: To find out the morbidity while repairing incisional hernia with abdominoplasty and comparing it with incisional hernia repair alone.Study Design: randomized prospective study Place and Duration of Study: This study was conducted at the Surgical Unit of Allama Iqbal Memorial Teaching Hospital Sialkot from Jan 2015 to Dec 2019.Materials and Methods: A total of 50 cases were randomized prospectively to compare the repair of incisional hernia isolated/combined with abdominoplasty. This is randomized prospective studies which is comparing two groups of patients, one small incisional hernia repair and second one repair of incisional hernia with abdominoplasty, in the general surgical unit of a teaching hospital.Results: The incidences were more in female as compared to male, significant relationship found between two groups regard to BMI (33.28 vs 34.96) (p 0.002), number of operation (p 0.001), defect size (p 0.001), mean hospital stay (p 0.001), insignificant relation found in regard to gender, residence, complications and recurrence (p-value>0.05).Conclusion: Post incisional hernia repair is still a challenge for surgeon to combine the two procedures to improve the quality of life with low morbidity and recurrences in well selected patients.